Rituximab, Omalizumab, and Dupilumab Treatment Outcomes in Bullous Pemphigoid: A Systematic Review - Cao, Peng; Xu, Wenjing; Zhang, Litao (Frontiers in Immunology, 2022)
Background Bullous pemphigoid (BP) is the most common autoimmune subepidermal bullous disease of the skin. First-line treatment of systemic corticosteroids may cause serious adverse events. Rituximab, omalizumab, and dupilumab should be explored as alternative treatment options to improve outcomes. Objective To systematically review the rituximab, omalizumab, and dupilumab treatment outcomes in bullous pemphigoid. Methods A PubMed, Embase, Web of Science, and Cochrane library search were conducted on March 10, 2022. A total of 75 studies were included using Preferred Reporting Items for Systematic Reviews and Meta-analyses guidelines. Results Use of rituximab (n=122), omalizumab (n=53) and dupilumab (n=36) were reported in 211 patients with BP. Rituximab led to complete remission in 70.5% (n=86/122) and partial remission in 23.8% (n=29/122) of patients within 5.7 months, with a recurrence rate of 20.5% (n=25/122). 9.0% (n=11/122) of patients died and infection (6.6%, n=8/122) was the most common adverse event. Omalizumab led to complete remission in 67.9% (n=36/53) and partial remission in 20.8% (n=11/53) of patients within 6.6 months, with a recurrence rate of 5.7% (n=3/53). 1.9% (n=1/53) of patients died and thrombocytopenia (1.9%, n=1/53) was observed as the most common adverse event. Dupilumab led to complete remission in 66.7% (n=24/36) and partial remission in 19.4% (n=7/36) of patients within 4.5 months of treatment without any reported adverse events, with a recurrence rate of 5.6% (n=2/36). Conclusions Rituximab, omalizumab, and dupilumab have similar clinical benefits for BP patients. However, rituximab resulted in higher recurrence rates, adverse events, and mortality rates. Systematic Review Registration https://www.crd.york.ac.uk/PROSPERO/, identifier CRD42022316454.